Pengaruh Strategi Pembelajaran Critical Incident Terhadap Keterampilan Menulis Teks Eksplanasi Pada Siswa Kelas VII SMPN 2 Cikampek - Wahidah, Siti; Supriadi, Oding; Sugiarti, Dewi Herlina (Peneliti.net, 2024)
This research was motivated by problems found in the field that students had difficulty in writing explanatory texts, besides that the problems began due to students' lack of interest in writing and the use of inappropriate learning strategies. The study aims to (1) Describe the application of critical incident learning strategies to the ability to write explanatory texts in grade VII students of SMP Negeri 2 Cikampek, (2) Describe student learning outcomes in the application of critical incident learning strategies to the ability to write explanatory texts in grade VII students of SMP Negeri 2 Cikampek. The author uses a quantitative approach with quasi-experimental methods and nonequivalent control group design. The correlation between the research design and the objectives of this study is the use of two classes that will be compared before and after receiving treatment. Research processing using SPSS software version 26. This research was conducted at SMP Negeri 2 Cikampek by taking two classes as samples, namely classes 7G and 7J, each consisting of 40 students. The study sample was taken by purposive sampling. There are three stages in this study, namely pretest, treatment or treatment and posttest. Pretest is conducted to determine the initial ability of students in writing explanatory texts before getting treatment. After being given a pretest, researchers gave treatment using critical incident strategies for experimental classes, while control classes used conventional strategies. The next step is to give a posttest to students to see the influence of the strategy used. Based on the results of the study, it was stated that the average score of the experimental class pretest and posttest scores were 44.9 and 78.4 and it showed that the posttest and pretest scores had a difference of 33.5. While the average score of the control class pretest and posttest scores of 43.1 and 61.3 shows that the two scores have a difference in value of 18.3. This shows that the experimental class is higher than the control class. Furthermore, the results of the hypothesis test with a significant level of 0.000 < 0.05 which means Ho is rejected and Ha is accepted and the hypothesis test of N-gain value with a significant level of 0.000 < 0.05 which means Ho is rejected and Ha is accepted. Thus, the conclusion is that there is an influence of critical incident learning strategies in the ability to write explanatory texts in grade VII students of SMP Negeri 2 Cikampek.